Scalable Python Tools for Managing OTA Updates in Automotive Systems - Palanichamy, Karthikeyan (International Journal of Scientific Research and Management (IJSRM), 2023)
Over-the-air (OTA) updates have revolutionized the automotive industry by enabling remote updates of software in vehicles, offering improved functionality, security patches, and bug fixes without requiring physical intervention. Python, with its versatility and rich ecosystem, presents a promising framework for developing scalable tools to manage OTA updates efficiently in automotive systems. This paper reviews current literature and explores various Python-based approaches, frameworks, and tools for implementing and managing OTA updates in automotive systems, highlighting their advantages, challenges, and future research directions.